Facial height in Japanese-Brazilian descendants with normal occlusion - Fabiano Paiva Vieira; Arnaldo Pinzan; Guilherme Janson; Thais Maria Freire Fernandes; Renata Carvalho Sathler; Rafael Pinelli Henriques (Dental Press Editora, 2014)
OBJECTIVE: The aim of this study was to determine the standards of facial height in 30 young (14-year-old) Japanese-Brazilian descendants with normal occlusion, and assess whether sexual dimorphism is evident. METHODS: The cephalometric measurements used followed the analyses by Wylie-Johnson, Siriwat-Jarabak, Gebeck, Merrifield and Horn. RESULTS: Results showed dimorphism for total anterior facial height (TAFH), lower anterior facial height (LAFH), anterior facial height (AFH), total posterior facial height (TPFH) and upper posterior facial height (UPFH) measurements. CONCLUSIONS: The standards of facial heights in young Japanese-Brazilian descendants with normal occlusion were observed. Sexual dimorphism was identified in five out of thirteen evaluated variables at this age range.